Enhanced pro-coagulant hemostatic agents based on nanometric zeolites - Laurenti, Juliana Bergamasco [UNESP]; Zazeri, Gabriel [UNESP]; Povinelli, Ana Paula Ribeiro [UNESP]; de Godoy, Moacir Fernandes; Braile, Domingo Marcolino; da Rocha, Tânia R. Flores; D' Amico, Élbio Antônio; Nery, José Geraldo [UNESP] (Elsevier, 2017)
Micro-and nanometric faujasite zeolites were tested as hemostatic coagulant agents. The as-made zeolites and their calcium ion exchanged derivatives were characterized by XRD, SEM, AFM, TGA, and DSC. Zeta potential measurements of the micro and nanometric zeolites, as a function of pH (1–12.5), revealed the hemostatic potential of the materials. The isoelectric point for FAU, FAU/Ca, Nano-FAU, and Nano-FAU/Ca were measured at pH 2.0, 1.9, 3.2, and 2.5, respectively. The hemostatic activity was confirmed by the TEG technique for both micro and nanometric zeolites, however a superior activity were observed for the nanometric materials. FAU and FAU/Ca exhibited a reduction of the R parameter (defined as period of time of latency from the start of test to initial fibrin formation for the formation of a clot of an amplitude of 2 mm) from 8.6 ± 0.7 min (control) to 3.2 ± 0.7 min and 2.3 ± 0.1 min, respectively. On the other hand, for the Nano-FAU, and Nano-FAU/Ca the observed decrease were to 2.4 ± 0.6 min, and 1.1 ± 0.2 min, respectively. The amounts of heat released were 105.60 J/g (FAU), 65.8 J/g (FAU/Ca), 85.48 J/g (Nano-FAU), and 78.21 J/g (Nano-FAU/Ca). Statistical analysis using one-way analysis of variance showed a global value of p < 0.0001. Tukey-Kramer multiple comparisons revealed significant (p < 0.0001) differences for FAU, FAU/Ca, Nano-FAU, and Nano-FAU/Ca, relative to the control. Nano-FAU/Ca showed the most important reductions of the R with significant differences compared to the control (p < 0.0001 and p < 0.0001, respectively) and FAU (p = 0.0071 for the R parameter).
Keywords: Hemorrhage; Hemostatic agents; Inorganic; Nanometric zeolites